(3QSGdI aj LeY QCji CadGWhf hCQSWhs - (3ESeGYjd Hf MeGO GdLhgQj , CHh fUQ, J (B393 (3g` s
(3ChdgG (B:s
(3GdMeO dhGgH GdYbd heHOYI gPg ebGdI CHj fUQ GdaGQGHi ai GdLeY Hjf QCji CadGWhf hCQSWh Cfi deG QCjJ CcKQ CLd ReGffG bO NGVhG hJfGRYhG ai MOhK GdYGde hbOeI s
(3BNQgG (B:s
(3hdfNJe Gdbhd ajeG QefG HjGfI ai GdLeY Hjf QCji GdMcjejf CadGWhf hCQSWh hGdMeO ddg Mb MeOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B21s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B267s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B_ (3GdfLa (B(369) s
Keywords: (3GdeLGejYs